Impact of Clavicular Shortening after Midclavicular Fracture: A Retrospective Series - Axel Jubel; Gereon Schiffer; Jonas Andermahr; Christoph Faymonville (Open Journal of Trauma - Peertechz Publications, 2017)
Background: Clavicular shortening often occurs after midclavicular fractures and its impact on functional outcomes has thus far been evaluated solely by radiographic and surgeon-based measures, with divergent findings. The goal of this study was to evaluate shoulder function and disability after midclavicular fractures in relation to shortening and compare it with that of healthy individuals and individuals with nonunion. Methods: Seventy-one adult patients (38±14 years) with midclavicular fractures that had been treated nonoperatively were reviewed retrospectively after a mean follow up of 28±15 months.The primary outcome variables were Disabilities of the Arm, Shoulder, and Hand, Constant-Murley, and Cologne clavicle scores. Range of motion was calculated as the difference in degrees between the injured and uninjured sides. Control cohorts of 35 healthy adults and 28 persons with nonunion were assembled. Results: Average shortening was 1.2±0.75 cm. Patients with clavicular shortening of >2 cm (Group 3) had signifi cantly more pain, greater loss of mobility and lower Constant-Murley scores than patients with shortening < 1 cm (Group 1) and healthy controls. Shortening deformity of more than 2 cm associated  with Disabilities of the Arm, Shoulder, and Hand, Constant-Murley, and Cologne clavicle equivalent to those of subjects with nonunion. Shortening deformity of more than 2 cm is functionally equivalent to nonunion. Conclusions: Shortening deformities after clavicular fractures in adults greatly impact functional outcomes. Patients perceive a shortening deformity of ≥ 2cm as conferring significant disability. These findings  suggest that the goal of therapy for diaphyseal clavicular fractures should be restoration of anatomical  length of the clavicle.